Association between dietary components and gut microbiota: a Mendelian randomization study - CHEN Haimiao, MA Yan, LIU Mingqi, MA Shanshan, LI Jun, XU Laichao (预防医学)
Objective: To explore the causal association between dietary components (carbohydrate, fat, protein, and sugar) and 119 genera of known gut microbiota using Mendelian randomization (MR) methods. Methods: Genome-wide association study (GWAS) data for dietary components were collected from the DietGen, while GWAS data for gut microbiota were collected from the MiBioGen. Single nucleotide polymorphism (SNP) loci associated with the four dietary components were used as instrumental variables, and 119 known gut microbiota genera were used as the outcomes. MR analysis was performed using inverse variance weighted (IVW) method. Heterogeneity was evaluated using Cochran's Q test, horizontal pleiotropy and exclude outliers were tested using MR-Egger regression and MR-PRESSO test. Common genetic pleiotropic genes between dietary components and gut microbiota were identified by MAGMA and PLACO analyses. Results: The MR analysis revealed causal associations between carbohydrates and 4 gut microbiota genera, fats and 14 genera, proteins and 14 genera, and sugars and 11 genera (all P<0.05). The MR-Egger regression analysis showed no horizontal pleiotropy among the selected SNPs, and the MR-PRESSO test did not identify any outliers (all P>0.05). The MAGMA and PLACO analyses revealed that 74.42% (32/43) of the causal associations had pleiotropic genes, with 1 to 10 pleiotropic genes identified. Multiple causal association groups shared the same pleiotropic genes. Conclusion: There are potential genetic and causal associations between dietary components and gut microbiota.